PENGARUH PROGRAM TAX AMNESTY TERHADAP FAKTOR-FAKTOR YANG MEMENGARUHI KEMAUAN MEMBAYAR PAJAK (STUDI PADA WAJIB PAJAK ORANG PRIBADI PELAKU USAHA DI WILAYAH KPP PRATAMA KOTA/KAB BOGOR) - Dinda Hawa; Yohanes Indrayono; Haqi Fadillah (JIAFE (Jurnal Ilmiah Akuntansi Fakultas Ekonomi), 2018)
Taxes are the largest source of funding for the state infrastructure development, this requires the citizen participation for their implementation. This can be shown by the obedience and the willingness to pay taxes. Obedience is shown by the willingness of the taxpayer to register, have NPWP, calculate and pay taxes, and also report SPT. Each year the compliance ratio shows an increase, but the realization of SPT is far from the amount of the taxpayer that must submit SPT. This indicates that taxpayers do not have the factors of willingness to pay taxes, especially a lot of taxpayers who save and distribute their funds abroad. So the government issued tax amnesty policy to grow the state revenue, increase tax compliance and taxpayer's willingness to pay and report tax. This study aims to knowing and explaining the effect of tax amnesty program to the willingness of paying tax of the individual entrepreneur tax payers that registered at KPP Kota/Kabupaten Bogor. This study was a quantitative research that used primary data obtained through questionnaire distribution to 100 respondents who are individual entrepreneur tax payer in the city and/or district of Bogor wthe the sampling technique used in this study is convenience sampling or also known as accidental sampling. The data was analyzed by multiple regression using PLS 3.0 for student programs. The result showed that based on Ha accepted, it indicates that there is a positive influence between the tax amnesty program variable on the willingness of paying tax variables, that is tax amnesty has a positive effect on awareness of paying taxe, aknowledging and understanding of taxation regulation, good perception on tax system effectiveness, and tax sanction.  This means that tax amnesty program responded positively by the increasing of willingness to pay taxes.